Exploring cultural influences on engagement in peer review through the lens of self-determination theory at a transnational university in China. (1st March 2022) - Collett, David; Evans, Sam; Hu, Mian
Abstract : Peer review (PR) in higher education is increasingly used to improve the quality of students' writing. This study uses Deci and Ryan's (1985) self-determination theory as a framework to explore postgraduate students' engagement with PR training on an eight-week pre-sessional (PSE) training programme at a transnational university in China. With the aim of improving English for Academic Purposes (EAP) students' engagement in the PR process, a four-layered model was developed to embed PR within the PSE curriculum. Qualitative data was gathered during the course from forty-six reflective essays. Follow-up data was collected from a focus group six months after the course to investigate students' continued engagement with PR during their master's programmes. Results indicate that although the PR training programme improved students' engagement, opportunities for using and extending their use of PR into their master's programmes were limited owing to lack of autonomy.